The Impact of Implementing the Modular Professional Nursing Practice Model on Nurse Work Motivation at Unicare Clinic Bali - Nugrahini, Ni Luh Gede Hari; Suyasa, I Gede Putu Darma; Adianta, I Ketut Alit; Agustini, Ni Komang Tri (Babali Publisher, 2024)
Background: The implementation of the Professional Nursing Practice Model (PNPM) has not been carried out by all health institutions in Indonesia, which causes the work of nurses to be less effective and affects nurses' work motivation. This study aimed to determine the impact of PNPM on nurses’ motivation at Unicare Clinic Bali. Methods: This study used a quasi-experimental design with a control group. A total sampling method involved 140 nurses divided into intervention and control groups. The variables identified were the components of work motivation, which consist of organizational culture, leadership, communication, work activities, and compensation. The research instrument used was a standard work motivation questionnaire based on Herzberg's theory. Data analysis was conducted using a paired t-test to measure the difference between the control and intervention groups and an independent t-test to determine the difference between intervention groups. Results: The results showed differences in nurses' work motivation scores in the intervention group before and after the intervention. There is a significant difference between work motivation between the intervention and control groups with t-value 2,432> t-table 1,667 tables and p value<0.05. Conclusion: There was an increase in nurses' work motivation components in applying the Modular PNPM. Nurses can play an active role in providing suggestions to improve the quality of nursing services, and evaluation of the PNPM can be carried out on an ongoing basis to maintain its effectiveness and efficiency.